The impact of obesity on sexual functioning among women - Ciechacka, Maria; Pawełko, Agnieszka; Bąk, Ewelina (Journal of Education, Health and Sport, 2025)
Introduction Psychological problems also lead to sexual disorders in obese patients: low self-esteem, lack of acceptance of one's body, depression leading to decreased libido. Physical appearance, including body weight, is one of the basic elements shaping a person's identity; it also fundamentally affects self-esteem. On its basis, an image of one's own body is created, which is an important part of one's self-image. Body image is the image formed in the mind, which is the way one's body appears to itself. Material and methods The research was carried out among 99 women, including 47 diagnosed with obesity and 52 without obesity. In this study, the diagnostic survey method was used. The research was conducted using the Female Sexual Function Index (FSFI) questionnaire. Results Obesity had a negative impact on all 6 domains of the FSFI and its overall score. The most negative feelings concerned the domain of excitement and the least negative ones concerned the domain of pain. Conclusions: Among obese patients, there is a negative impact of this disease on sexual aspects. Patients with obesity require greater focus on educational activities aimed at following a good diet, especially the Mediterranean diet, as well as systematic visits and compliance with therapeutic recommendations.